1987
DOI: 10.1002/ajpa.1330730204
|View full text |Cite
|
Sign up to set email alerts
|

Some secular changes in body height and proportion of Japanese medical students

Abstract: Anthropometric dimensions of 738 medical students at Kyushu University in Japan were analyzed to determine secular changes of height and body proportions during a 20-year period. Since 1961, means of standing height, leg length, and ratio of leg length to standing height have increased, although the rate of increase from 1971 to 1981 has been rather slow. On the contrary, the mean sitting height X 100/standing height has declined during this same period. Compared with data on the Japanese general population, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 7 publications
4
23
0
Order By: Relevance
“…It has been observed that the recent increase in height is mainly due to increase in leg length, rather than trunk length or sitting height (Yanagisawa and Kondo, 1973;Tanner et al, 1982;Ohyama et al, 1987). Figure 4 shows the secular changes in sitting height and leg length calculated as height minus sitting height.…”
Section: Statistical Reports On Anthropometric Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the recent increase in height is mainly due to increase in leg length, rather than trunk length or sitting height (Yanagisawa and Kondo, 1973;Tanner et al, 1982;Ohyama et al, 1987). Figure 4 shows the secular changes in sitting height and leg length calculated as height minus sitting height.…”
Section: Statistical Reports On Anthropometric Datamentioning
confidence: 99%
“…The Physical Strength series data indicate that the height difference between students and workers is due to the difference in sitting height, but the School Health and Nutrition series indicate that the height difference between students and the general population is due to both sitting height and leg length. Some investigators expect that the relative leg length of Japanese will eventually reach that of the European population (Ohyama et al, 1987), but when the proportions of present-day Japanese are compared with those of the European population of the same height, the difference is still clear (Hoshi, 1984). Takamura et al (1988) studied the secular changes in relative arm length (A/H) and arm length relative to sitting height (A/S) during the 26 years between 1961-62 and 1985-86.…”
Section: Statistical Reports On Anthropometric Datamentioning
confidence: 99%
“…A quite related instance of conservative change is the widely recognized secular acceleration of body size (Chamla, 1983;Haug, 1984;Sidhu et al, 1982). Through searches in the literature and direct evidence from our post-mortem material, it was not difficult to conclude that the Germans had already experienced a secular acceleration (Jolicoeur et al, 1988); the Japanese were in the middle of the process (Matsumoto, 1982;Ohyama et al, 1987), and the Brazilian group was at its beginning.…”
Section: Neural Aspects Of Aging Longevity and Expectation Of Lifementioning
confidence: 99%
“…Ohyama, S., Hisanga, A., Inamasu, T., Yamamoto, A., Hirata, M. & Ishinishi, N. (1987). Some secular changes in body height and proportion of Japanese medical students.…”
Section: Aknowledgementmentioning
confidence: 99%
See 1 more Smart Citation